Relevansi Pemikiran Filsafat Pendidikan Islam Ibn Sina dan Al-Ghazali terhadap Pendidikan Modern - Wahyudi Mutalib, Wahyudi; Mohammad Nahrawi; Ahmad Mujahidin; Febry Suprapto (Educational Research Center, 2025)
The philosophy of Islamic education has made a significant contribution to the development of contemporary educational theory and practice. Among its most prominent figures, Ibn Sina and Al-Ghazali occupy central positions, as both offer educational paradigms rooted in the integration of knowledge, ethics, and spirituality. This article aims to analyze the relevance of the educational philosophies of these two thinkers in the context of modern education, which tends to be pragmatic and secular. This study employs a library research approach with content analysis methods applied to Ibn Sina’s major works such as Kitab al-Shifa’ and Kitab al-Najat, as well as Al-Ghazali’s Ihya’ Ulum al-Din and Ayyuha al-Walad. The findings indicate that Ibn Sina emphasizes rationality and intellectual development as the path toward human perfection (al-insan al-kamil), while Al-Ghazali focuses on purification of the soul and the balance between rational and divine knowledge. In the context of modern education, the synthesis of their thoughts offers a holistic educational model that integrates intellectual, moral, and spiritual dimensions. Theoretically, this research enriches the discourse on the integration of knowledge and values within Islamic educational philosophy; practically, it provides a philosophical foundation for developing a character education curriculum oriented toward humanity and transcendence.